The combined effects of motor imagery and motor practice are influenced by differences in working memory function: Examination of brain, spinal cord, and muscle performance data - Yuki Fukumoto; Hiroki Bizen; Marina Todo; Naoki Yoshida; Toshiaki Suzuki (IBRO Neuroscience Reports)
The ability to perform motor imagery is affected by differences in short-term memory storage capacity in terms of the activation of working memory. Therefore, from the viewpoint of the simultaneous measurement of brain activation and spinal motor neuron excitability, we examined differences in the combined effects of motor practice and motor imagery due to differences in working memory function. 20 healthy individuals were classified into Normal (score of ≤5–6 digits) and Good (score of ≥7 digits) groups based on working memory in a digit span test. Following this, participants performed six sets of repetitive exercises combining motor practice and motor imagery, and changes in neural activity patterns in the brain and spinal cord, as well as changes in finger dexterity, were tracked. In brain network analysis, the first execution of the imagery showed high Betweenness Centrality in the frontal pole cortex, which shifted to the dorsolateral prefrontal cortex with repeated imagery. The involvement of the frontal pole may reflect introspection of motor behavior in the initial stage, while the dorsolateral prefrontal cortex consistently participated in imagery generation throughout the entire motor imagery process. In addition, both groups showed improvement in finger dexterity after intervention, but during repetitive motor imagery, a decrease in amplitude F/M ratio was observed in the Good Working Memory group, and a decrease in activation of the right primary motor cortex was observed in the Normal Working Memory group. In terms of working memory, especially in aspects of the phonological loop, those with higher function may execute motor imagery more distinctly.